A review of research and development of C4 rice / Intan Nur Ain Mohd Izlan - Mohd Izlan, Intan Nur Ain (Faculty of Plantation and Agrotechnology, 2018)
Rice is the world’s most important crop and a primary food source for half of the world’s population. Asian cultivated rice, Oryza sativa, is grown worldwide. Like other cereals such as wheat, maize, barley, sorghum, oats, and rye, which feed the world, rice belongs to the grass family Gramineae. Rice has shaped the culture, diets and economic of thousands of millions of peoples. Rice has its own benefit in every aspect. However, Rice has what is known as a C3 photosynthetic pathway, less efficient than that of maize, which has a C4 pathway. After all, insufficient yields of rice will produce food insecurity, unsustainable agricultural practices, environmental degradation and social unrest. To implement C4 pathway in rice, we need to focus on the characteristic of both C3 and C4 plant and as well as the latest strategies for development of the C4 rice. The anatomical and biochemical process in the rice are modified to become C4 rice. Every gene expression that needed to encode specific enzymes in order C4 plant characteristic can be develop inside rice are identified. This review eventually will provide knowledge and information on the current status in C4 rice development.